MUNAA Agriculture Market: Connecting Home to Abroad - Rizal, Govinda; Karki, Yogendra Kumar; Lama, Jiwan Prabha; Gurung, Yubaraj (Nepal Journal of Science and Technology, 2021)
Nepalese diaspora has globalized Nepal’s culture, tradition, value, festival, celebration, food, and goods. The Nepalese people have special liking of inherent tastes, flavor, ingredients, cuisine specificities, and indigenous commodities of Nepal. The Non-Resident Nepalese Association (NRNA) and its vast memberships abroad seek such commodities in places where they live. An organization under the Joint Cooperation of Agriculture Promotion Committee of NRNA, Mutual Understanding between NRNA and Agriculture Authority (MUNAA) Agriculture Limited, a company registered with the Bagmati Province with a mandate to work in all provinces of Nepal and abroad, has a mission to connect Nepalese people at home and abroad with the Nepalese agricultural products. MUNAA trades hygienic, safe, fresh, and processed Nepalese food products with the ‘safe food, safe life’ slogan under the ‘MUNAA’ brand. The government of Nepal has adopted favorable agricultural policies that aim to increase production sustainably, substitute imports, and expand export to minimize trade deficits. In addition to following government policies, MUNAA has plans to import technologies for value addition that will benefit both the producers and consumers as per the expectation of the government and Nepalese people at home and abroad.